An evaluation of the potential effect of behavioural biases on the investment patterns of individuals - Lipschitz, Isaac Daniel (My University, 2020)
Purpose: A saving and investing crisis exists in South Africa. Only 40% of South Africans have some form of a retirement plan. These savings deficiencies, whilst largely a function of economic inequality, are exacerbated by current economic conditions and inadequate personal financial planning. However, this lack of saving could also be partly attributed to a lack of rationality which manifests as behavioural biases. These behavioural biases cause individuals to make sub-optimal investment decisions. The purpose of this study is to determine the extent to which behavioural biases impact savings patterns of individuals. Methodology: Data on these biases, demographic information and financial literacy have been collected by means of a survey. 309 participants responded to the survey from June to August 2019. Participants are income-earning South Africans. Various proxies were used in order to quantify the behavioural biases. A factor analysis and MANOVA were performed. Originality/Value: This research has both theoretical and practical implications. Whilst a growing strand of research exists on behavioural finance in international markets, its application in a South African context is limited, particularly with regards to personal finance. In addition, the research has practical implications in the way fund managers and other investing service providers provide and present information to investors. This is one of the first studies which explores the effect of behavioural biases on individual’s financial decision-making processes within a South African context. Findings: Individuals are risk averse on average but appear not to understand risk from a financial perspective. Investors are short-termist and are prone to the behavioural bias of over confidence. As investors age and tend towards retirement, the trait of overconfidence declines. Individuals with higher financial literacy tend to invest at a younger age, leading to improved retirement outcomes
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Accounting), (50% Research), University of the Witwatersrand, 2020